Implementasi Peraturan Daerah Kota Palangka Raya Nomor 13 Tahun 2009 Tentang Pengaturan, Penertiban Dan Pengawasan Pedagang Kaki Lima Di Kecamatan Jekan Raya Kota Palangka Raya - Laksminarti Laksminarti (Pencerah Publik, 2020)
This study aims to analyze and describe the arrangements of street vendors in Jekan Raya sub-district, Palangka Raya city. The research method used is a qualitative research method, using data collection techniques through observation, interviews and documentation. Sources of data in this study are apparatus or agency employees and related parties with the implementation of street vendor regulation (PKL) policy. Based on the results of research Analysis of the arrangement of street vendors in Jekan Raya sub-district of Palangka Raya City is quite good, but the response from the public in providing information is still not good. Researchers indicate that the relevant agencies as implementing the regulation of street vendors have taken action in an effort to improve the motto of the City of Palangka Raya, namely the Beautiful City. However, the implementation in the field was not suitable as expected, there were still many obstacles because there were still many stubborn street vendors.